(untitled) (Jurnal Informatika dan Komputasi: Media Bahasan, Analisa dan Aplikasi, 2024)
An excellent way to disseminate important information to patients and all relevant stakeholders is through the hospital website. As regulated in Indonesian Law No. 8/2016, websites must be designed to meet the information needs of all people, including people with disabilities. Therefore, it is necessary to evaluate and determine how accessible hospital web pages are. This research uses the web content accessibility guidelines (WCAG 2.2) as an evaluation tool to evaluate the accessibility of the Kiwari Bandung Hospital web page. The results of the evaluation conducted with the Audioeye evaluation tool show that there are 60 accessibility violations, with the most violations in the link category, namely operable, understandable, and robust.